2003
DOI: 10.1021/jm020571x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Activity of Two Novel 1-Dodecylthio-2-decyloxypropyl-3-phosphatidic Acid Conjugates with Gemcitabine and Cytosine Arabinoside

Abstract: Cytosine arabinoside (ara-C) and gemcitabine (dFdC) are two standard chemotherapy drugs used in the treatment of patients with various cancers. To alter the pharmacokinetic and pharmacodynamic properties of these molecules, we conjugated a synthetic phospholipid to both ara-C and dFdC and investigated their chemotherapeutic potential. The dFdC conjugate had greater cytotoxic activity compared with the ara-C conjugate and demonstrated notable cytotoxicity against all human cell lines tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 14 publications
0
51
0
Order By: Relevance
“…Phase-II: synthesis of gemcitabine-(carbamate)-PMPI sulfhydryl-reactive intermediate Gemcitabine (10 mg/ml stock in DMSO) was combined with N-[p-maleimidophenyl]-isocyanate (PMPI) 65-67 at a 5:1 molar ratio in combination with constant gentle stirring at 25°C for 3.5 h so that the isocyanate moiety of PMPI which exclusively reacts with hydroxyl (R-OH) groups preferentially created a carbamate covalent bond at the terminal C 5 -methylhydroxy group of gemcitabine. 61,[68][69][70][71][72][73] The highly selective reaction is reportedly complete within 2 h under the applied conditions. Gemcitabine was formulated at a large molar excess to deplete un-reacted PMPI and maximize synthesis of the sulfhydryl-reactive maleimide intermediate as validated by high-performance thin-layer chromatography analysis (HP-TLC).…”
Section: Introductionmentioning
confidence: 87%
“…Phase-II: synthesis of gemcitabine-(carbamate)-PMPI sulfhydryl-reactive intermediate Gemcitabine (10 mg/ml stock in DMSO) was combined with N-[p-maleimidophenyl]-isocyanate (PMPI) 65-67 at a 5:1 molar ratio in combination with constant gentle stirring at 25°C for 3.5 h so that the isocyanate moiety of PMPI which exclusively reacts with hydroxyl (R-OH) groups preferentially created a carbamate covalent bond at the terminal C 5 -methylhydroxy group of gemcitabine. 61,[68][69][70][71][72][73] The highly selective reaction is reportedly complete within 2 h under the applied conditions. Gemcitabine was formulated at a large molar excess to deplete un-reacted PMPI and maximize synthesis of the sulfhydryl-reactive maleimide intermediate as validated by high-performance thin-layer chromatography analysis (HP-TLC).…”
Section: Introductionmentioning
confidence: 87%
“…This platform thus opens exciting prospects for the discovery of new anticancer nanomedicines with improved pharmacological activities on resistant cancer cells. 19 F and 31 P, respectively) spectrometers. Recognition of methyl, methylene, methine, and quaternary carbon nuclei in 13 C NMR spectra was based on the Jmodulated spin-echo sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the delivery of 2Ј,3Ј-disubstituted nucleotides remains troublesome. [19] In investigations directed towards overcoming these drawbacks, we recently reported that squalenoyl monophosphate nucleosides with antiviral or anticancer activities were also able to assemble into nanoparticles that displayed promising biological activities. [20] In this paper we give a full account of the synthesis of conjugate SQdFdC-MP (5, Figure 1), we provide key features about the supramolecular organisation of the nano-objects and finally we disclose new biological results relating to the efficacy of SQdFdC-MP towards gemcitabine-resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks of nucleoside therapeutics provoke a profound interest in the search of prodrugs exhibiting an effectiveness superior to that of the parent drug. Among such derivatives, conjugates of nucleosides and phospholipids attracted attention and it was demonstrated that these derivatives display advantageous biological properties over free nucleosides (Ryu et al 1982;Shuto et al 1995;Vodovozova et al 1996;Herrmann et al 1997;Brachwitz et al 1998Brachwitz et al , 1999Kucera et al 1998;Mavromoustakos et al 2001;Alexander et al 2003; for a review, see Morris-Natschke et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical synthesis of phospholipid-D-nucleo side conjugates has been achieved (Brachwitz et al 1998(Brachwitz et al , 1999Mavromoustakos et al 2001;Alexander et al 2003; for a review, see Rosemeyer 2005) though enzymatic and chemo-enzymatic methods also exist (Shuto et al 1995, and references cited therein). An application of PLD as a biocatalyst for the preparation of such conjugates is very efficient (Shuto et al 1995) and these data prompted us to study an enzymatic synthesis of nucleoside-phospholipid conjugates employing phospholipase D (PLD; EC 3.1.4.4) as a biocatalyst.…”
Section: Introductionmentioning
confidence: 99%